Effect of Fiber Length on The Composite Properties of Salacca zalacca Pellet Fibers – Epoxy - Andreas; Sinuhaji, Perdinan (Talenta Publisher, 2022)
Research on the effect of fiber length on the physical and mechanical properties of composite fibers has been conducted, with variations in fiber lengths of 1 cm, 1.2 cm, 1.4 cm, and 1.6 cm, each added Epoxy and Hardener 1: 1 then stirred by the Hand Lay Up method and pressed for 20 minutes at a temperature of 90ºC. The characterization of composite physical properties showed a density value of 1.1325 g/cm3, porosity by 1.53%, and water absorption by 1.33%. The physical properties of composites have met the standard SNI 03-2105-2006 and can be used as a composite replacement material. The characterization of the composite mechanical properties shows a maximum bending strong value of 25.15 kgf – 40.12 kgf, tensile strength of 11.31 MPa – 15.37 MPa, and a strong impact of 50.43 J/mm2-80.93 J/mm2 has met high impact ABS quality standards of 13.48 J/m2. All mechanical properties of the composite meet the JIS A 5905:2003 standard.